Exploration of Targeted Anti-Tumor Therapy 2020
DOI: 10.37349/etat.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

Development of PROTACs to address clinical limitations associated with BTK-targeted kinase inhibitors

Abstract: Chronic lymphocytic leukemia is a common form of leukemia and is dependent on growth-promoting signaling via the B-cell receptor. The Bruton tyrosine kinase (BTK) is an important mediator of B-cell receptor signaling and the irreversible BTK inhibitor ibrutinib can trigger dramatic clinical responses in treated patients. However, emergence of resistance and toxicity are major limitations which lead to treatment discontinuation. There remains, therefore, a clear need for new therapeutic options. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 107 publications
0
27
0
Order By: Relevance
“…As expected, ibrutinib activity is highly susceptible to the C481S mutation due to this loss of covalent binding; a 74-fold potency decrease has been observed between mutant and wild-type BTK [ 51 ]. PROTACs are emerging as a promising alternative to circumvent the resulting ibrutinib resistance, with many examples now reported [ 52 ]. For example, PROTAC 16 ( Figure 5 ), developed by Sun et al [ 53 ], was able to degrade both wild-type and C481S mutant BTK with nanomolar potencies.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, ibrutinib activity is highly susceptible to the C481S mutation due to this loss of covalent binding; a 74-fold potency decrease has been observed between mutant and wild-type BTK [ 51 ]. PROTACs are emerging as a promising alternative to circumvent the resulting ibrutinib resistance, with many examples now reported [ 52 ]. For example, PROTAC 16 ( Figure 5 ), developed by Sun et al [ 53 ], was able to degrade both wild-type and C481S mutant BTK with nanomolar potencies.…”
Section: Introductionmentioning
confidence: 99%
“…BTK-PROTACs have demonstrated advantages for overcoming the drug resistance and toxicity of BTK inhibitors. To identify orally bioavailable BTK-PROTACs, statistical methods such as PCA and DA were applied to identify the key structural features that may contribute to the oral absorption of PROTACs. After easing the interpretation and readability of the data of the structural features generated from the groups of drugs with MW < 500, MW > 500, LOB-PROTACs, and OB-PROTACs, we used a systematic investigation of model molecules to verify the features.…”
Section: Discussionmentioning
confidence: 99%
“…PROTACs are structurally composed of a target protein–ligand, a linker, and an E3 ubiquitin ligase ligand. BTK-PROTACs, including P13I and L18I , have been reported previously that demonstrate potential in overcoming drug resistance and off-target effects of ibrutinib. Previous studies also showed that reversible covalent BTK-PROTACs, such as RC-1 , had better degradation activity and selectivity than irreversible covalent BTK-PROTACs (Figure ). However, a major challenge preventing the widespread therapeutic application of PROTACs is their route of delivery, which limits oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reversible BTK inhibitors such as fenebrutinib, rilzabrutinib, spebrutinib, ARQ 531, and LOXO-305 are currently being evaluated in clinical trials ( Estupinan et al, 2021 ). The second strategy is to develop BTK-targeted PROTACs ( Arthur et al, 2020 ), and several groups have explored this option. Because irreversible binding to the POI will likely negate the catalytic nature of PROTACs, reported BTK-PROTACs are mostly based on non-covalent inhibitors or convert irreversible inhibitors to reversible covalent binders ( Kiely-Collins, et al, 2021 ).…”
Section: Protacs Targeted Towards Treatment Of Various Types Of Drug ...mentioning
confidence: 99%